2012
DOI: 10.1590/s0101-20612012005000070
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory changes in aged sugarcane spirit submitted to filtering with activated carbon filter

Abstract: Physicochemical and sensory changes in aged sugarcane spirit submitted to filtering with activated carbon filter Alterações físico-químicas e sensoriais de cachaças envelhecidas submetidas à filtragem com carvão ativado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The concentration of methanol was not influenced by the treatment employed in this study, the data corroborate that found by Lima et al (2006; and by Duarte et al (2012).…”
Section: Adsorption Isothermssupporting
confidence: 91%
“…The concentration of methanol was not influenced by the treatment employed in this study, the data corroborate that found by Lima et al (2006; and by Duarte et al (2012).…”
Section: Adsorption Isothermssupporting
confidence: 91%
“…The assessments of the cachaça samples were performed in four sessions, each of which dealt with the evaluation of five samples of cachaças according to the methodologies proposed by Duarte et al (2012) for quantitative descriptive analysis. From this procedure, a spreadsheet was generated with the definition of descriptive terms (Duarte et al, 2012;Rota et al, 2013). The assessment environment had natural lighting complemented by white artificial light and a temperature of 22° C. The samples provided to the tasters were served in coded ISO glasses, in a volume of 15 mL.…”
Section: Assessment Of Sensory Qualitymentioning
confidence: 99%
“…() evaluated sugarcane vinegar on the sensory basis and found it to be of good quality with the special fragrant flavor of the sugarcane, while Duarte et al . () reported a decrease in furfural acid in sugarcane spirits when subjected to storage after filtration through activated charcoal.…”
Section: Resultsmentioning
confidence: 98%